2005
DOI: 10.1080/13625180500279763
|View full text |Cite
|
Sign up to set email alerts
|

The unmet need for contraception among Nigerian women in the first year post-partum

Abstract: There is a need to study in more detail the social and cultural factors that determine contraceptive utilization before success can be achieved in closing the gap of unmet need, as it has become evident that increasing the awareness and knowledge of contraception is not enough to achieve the objectives of family-planning programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 11 publications
6
38
2
Order By: Relevance
“…Regardless of menstrual status, women 0-5 months postpartum who are exclusively breastfeeding are unlikely to have ovulatory cycles; for these women, ovulation returns later in the first year or once other foods are introduced [16]. Research has shown that postpartum women misunderstand the return to fecundity [18,[26][27][28]. This is true even among self-reported LAM users: a recent analysis of DHS data showed that many did not adhere to all three criteria for LAM effectiveness at the time of the survey [29].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of menstrual status, women 0-5 months postpartum who are exclusively breastfeeding are unlikely to have ovulatory cycles; for these women, ovulation returns later in the first year or once other foods are introduced [16]. Research has shown that postpartum women misunderstand the return to fecundity [18,[26][27][28]. This is true even among self-reported LAM users: a recent analysis of DHS data showed that many did not adhere to all three criteria for LAM effectiveness at the time of the survey [29].…”
Section: Discussionmentioning
confidence: 99%
“…It promotes the health of mothers and children by lengthening pregnancy interval and helps to avoid financial, psychological, and health costs due to unintended pregnancies. However, following childbirth many families overlook contraception due to a poor perception of pregnancy risks, difficulty in accessing services, and sociocultural issues [5, 6]. Many factors such as geographical and financial access, provider bias, poor method choice, lower status of women, medicolegal restrictions, and fear of side effects act as a barrier to family planning use [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of postpartum women indicate a desire to delay a next birth, FP methods are often not offered to, or taken up by, women after delivery or in the first year postpartum [3,5-7]. Based on the Health Belief Model, which has been widely used in the study of contraceptive use, perceived threat (perceived susceptibility and perceived severity), perceived benefits, cues to action, and self-efficacy are known to influence contraceptive behaviors [8-10].…”
Section: Introductionmentioning
confidence: 99%